2020
DOI: 10.1101/2020.05.02.073585
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Drosophilainsulin-like peptide 8 (DILP8) in ovarian follicle cells regulates ovulation and metabolism

Abstract: In Drosophila eight insulin-like peptides (DILP1-8) are encoded on separate genes. These DILPs are characterized by unique spatial and temporal expression patterns during the lifecycle. Whereas functions of several of the DILPs have been extensively investigated at different developmental stages, the role of DILP8 signaling is primarily known from larvae and pupae where it couples organ growth and developmental transitions. In adult female flies, a study showed that a specific set of neurons that express the D… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…As arthropod relaxin shares what seem to be the structural characteristics common to both aIGF and neuroendocrine insulins, it seems plausible that relaxin can also stimulate the insulin RTK. It is of interest in this respect that Drosophila relaxin, ilp7, binds to the decoy insulin receptor as well other Drosophila ilps (Okamoto et al, 2013) and previous work suggested that it acts through the Drosophila RTK (Linneweber et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…As arthropod relaxin shares what seem to be the structural characteristics common to both aIGF and neuroendocrine insulins, it seems plausible that relaxin can also stimulate the insulin RTK. It is of interest in this respect that Drosophila relaxin, ilp7, binds to the decoy insulin receptor as well other Drosophila ilps (Okamoto et al, 2013) and previous work suggested that it acts through the Drosophila RTK (Linneweber et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Insulin and related peptides typically stimulate growth and reproduction, so its presence in the ovaries and testes suggests a function in reproduction. Its presence in unfecundated eggs of Blattella suggests that within the ovary it are the oocytes themselves that express gonadulin, likely the follicle cells that in Drosophila have been shown to express Drosophila ilp 8 (Liao & Nässel, 2020). In the crab Portunus trituberculatus gonadulin expression is on occasion very high in the gonads (Veenstra, 2020), but the very variable degree of expression makes it difficult to see this hormone as merely stimulating reproduction.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations